The U.S. dollar exchange rate and the demand for oil - Selien De Schryder; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using recent advances in panel data estimation techniques, we find that an appreciation of the US dollar exchange rate leads to a significant decline in oil demand for a sample of 65 oil-importing countries. The estimated effect turns out to be much larger than the impact of a shift in the global crude oil price expressed in US dollar. Furthermore, the effect of the US dollar on oil demand tends to be declining over time and, for a subsample of OECD countries, stronger for an appreciation compared to a depreciation of the US dollar.
Keywords: C33; F31; Q41; 330; oil demand; US dollar exchange rate; panel data; nonlinearities